2022
DOI: 10.1186/s40104-022-00677-4
|View full text |Cite
|
Sign up to set email alerts
|

Chronic corticosterone disrupts the circadian rhythm of CRH expression and m6A RNA methylation in the chicken hypothalamus

Abstract: Background Corticotropin-releasing hormone (CRH), the major secretagogue of the hypothalamic-pituitary-adrenal (HPA) axis, is intricately intertwined with the clock genes to regulate the circadian rhythm of various body functions. N6-methyladenosine (m6A) RNA methylation is involved in the regulation of circadian rhythm, yet it remains unknown whether CRH expression and m6A modification oscillate with the clock genes in chicken hypothalamus and how the circadian rhythms change under chronic str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Hao et al showed that METTL3-mediated m6A modification plays an important role in biological processes such as mouse embryo development ( 8 ). Yang et al found that RNA m6A modification is involved in the regulation of circadian rhythms in the chicken hypothalamus under both basal and chronic stress conditions ( 9 ). m6A modification also has many functions in embryonic stem cell differentiation, development of the nervous and hematopoietic systems, myogenesis, zygote formation, and embryonic development ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hao et al showed that METTL3-mediated m6A modification plays an important role in biological processes such as mouse embryo development ( 8 ). Yang et al found that RNA m6A modification is involved in the regulation of circadian rhythms in the chicken hypothalamus under both basal and chronic stress conditions ( 9 ). m6A modification also has many functions in embryonic stem cell differentiation, development of the nervous and hematopoietic systems, myogenesis, zygote formation, and embryonic development ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation is that circadian patterns of hormone activities or concentrations are controlled by the duration of photophase, as has been shown in other investigations [ 56 ]. The secretion of CORT is regulated by the hypothalamic–pituitary–adrenal axis (HPA-axis) via the adrenocorticotrophic hormone (ACTH) and local adrenocortical catecholamine secretion [ 57 , 58 ]. Considering the influence of light on CORT production, an increased photoperiod under stable conditions is able to stimulate gonadotropine-releasing hormone (GnRH) secretion, which, in turn, enhances steroid production [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…So, the difference of central circadian system of chickens and mammals could be the major cause for this issue. Additionally, monochromatic light (e.g., green and red light) and chronic corticosterone had a significant impact on the expression pattern of circadian genes in the hypothalamus of chickens [6,32].…”
Section: Discussionmentioning
confidence: 99%